Strengthening The Self, Restoring The Soul: Self-Esteem As A Key To Psychological Well-Being In Women Survivors Of Sexual Violence - Tamara, Adi; Dearly, Dearly (Universitas Mercu Buana, 2025)
Cases of sexual violence are increasing where the impact of acts of sexual violence is not only physical but also psychological. This research was conducted on a group of women survivors of sexual violence. Because of the increasing number of cases of sexual violence and the group of women who are vulnerable or experience the most acts of sexual violence. The purpose of this study was to determine whether there is the role of self-esteem on psychological well-being in women survivors of sexual violence. Researchers have a hypothesis that self-esteem plays a role in the psychological well-being of women survivors of sexual violence. In this study using quantitative methods with simple linear regression analysis technique, sampling by accidental sampling technique, and the subjects in this study found 182 women survivors of sexual violence with a vulnerable age of 18-40 years. The measuring instrument used for psychological well-being uses the Ryff psychological well-being and the measuring instrument for self-esteem from Rosenberg. The results showed that there was a significant positive role between self esteem and psychological well-being in women survivors of sexual violence. So it can be interpreted that the condition of psychological well being can be improved by increasing self-esteem in women survivors of sexual violence